Platelets Levels before and after Surgical Intervention in Patients with Oral and Maxillofacial Tumors at MNH, Tanzania - Moshy, Jeremiah; Sohal, Karpal Singh; Owibingire, Sira Stanslaus; Augustino, Arnold (Scientific Research, 2015)
Background: There are documented effects of platelets on the solid tumors which need further study. The elevated platelet counts have been described for majority of cancers. There is inadequate information of effect of benign and malignant oral and maxillofacial tumors on the regulation of platelets. The aim of this study was to investigate the changes in platelet counts among patients with oral and maxillofacial benign and malignant tumors following surgical interventions. Methods: A descriptive postoperative study was done whereby patients with benign and malignant oral and maxillofacial tumors who met the inclusion criteria were included. The included patients were those who had no history of blood transfusion prior, during or after surgery, not on haemoglobin-boosting or bone marrow suppressing medications, not seropositive to human immunodeficiency virus also without clinical findings suggestive of lymphadenopathy, splenomegaly, ecchymosis and petechiae. Demographic data, Platelet counts and haemoglobin levels before and after surgery were documented and analysed by chi-square test and values were considered to be significant if p < 0.05. Results: A total of 61 patients were included in the study. The mean age of participants was 37.03 ± 16.6 years with range of 7 to 77 years. Majority 82.5% (n = 52) had benign tumors with a leading diagnosis of ameloblastoma followed by ossifying fibroma. In general there was an increase of platelet counts following surgery from the mean of 276.38 ± 109.40 K/uL to 308.51 ± 117.24 K/uL. Looking at benign and malignant separately, following surgery there was an increase of platelet counts for benign tumors (278.87 ± 106.37 to 305.96 ± 123.12) but a decrease for malignant tumors group (282.33 ± 147.03 to 232 ± 78.48). The haemoglobin level changed from the mean of 12.60 ± 1.71 g/dl before surgery to 11.69 ± 1.70 g/dl after surgery. Conclusion: The mean postoperative increase in platelet counts in benign and malignant tumors was due to healing process of the wound following surgery while the postoperative decrease in platelets counts in malignant tumors was due to effect of tumor removal which diminished the production of platelets activating factors. Malignant tumors produce platelets activating factors which are necessary for them to grow. Also, the difference in postoperative platelets counts in benign and malignant oral and maxillofacial tumors could be attributed by different biological behavior of benign and malignant tumors and hence different interactions of platelets to these tumors.
Keywords: Oral Maxillofacial Tumors; Pre-Operative Platelets Levels; Post-Operative Platelets Levels